2012
DOI: 10.4012/dmj.2012-054
|View full text |Cite
|
Sign up to set email alerts
|

Surface hardness of different restorative materials after long-term immersion in sports and energy drinks

Abstract: The purpose of this study was to evaluate the effect of sports and energy drinks on the surface hardness of different restorative materials over a 6-month period. Forty-two disk-shaped specimens were prepared for each of the four restorative materials tested: Compoglass F, Filtek Z250, Filtek Supreme, and Premise. Specimens were immersed for 2 min daily, up to 6 months, in six storage solutions (n=7 per material for each solution): distilled water, Powerade, Gatorade, X-IR, Burn, and Red Bull. Surface hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 36 publications
3
51
1
4
Order By: Relevance
“…However, citric acid has been shown to be aggressive for dental hard tissues and resin-based restorative materials. [13] The influence of the acidity increasingly dissolves the matrix, along with any unstable glass particles in a low pH value drink. High acidity might have a greater softening effect on the resin matrix, thus promoting the dislodgement and leaching out of filler particles and reducing the load resistance of restorative materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, citric acid has been shown to be aggressive for dental hard tissues and resin-based restorative materials. [13] The influence of the acidity increasingly dissolves the matrix, along with any unstable glass particles in a low pH value drink. High acidity might have a greater softening effect on the resin matrix, thus promoting the dislodgement and leaching out of filler particles and reducing the load resistance of restorative materials.…”
Section: Discussionmentioning
confidence: 99%
“…High acidity might have a greater softening effect on the resin matrix, thus promoting the dislodgement and leaching out of filler particles and reducing the load resistance of restorative materials. [13] In comparison to a giomer, resin composite was found to be less affected by low pH beverages or acid solution. [13] Therefore, Premise resin composite exhibited less change in surface hardness values than Beautifil II giomer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface degradation of RBCs were associated with the pH and the titratable acidity, which corresponds to previous studies. 23,26,27 Moreover, many studies have shown that acids might change the physical properties of RBCs under acidic conditions over time, [16][17][18][19][20] succinic acid, and 0.06% ascorbic acid. However, citric acid has been claimed to be erosive for dental hard tissues and RBC materials.…”
Section: Tablementioning
confidence: 99%